Designed di-heme binding helical transmembrane protein - Mahajan, Mukesh (2014)
De novo designing of functional membrane proteins is fundamental in terms of understanding the structure, folding, and stability of membrane proteins. In this work, we report the design and characterization of a transmembrane protein, termed HETPRO (HEme-binding Transmembrane PROtein), that binds two molecules of heme in a membrane and catalyzes oxidation/reduction reactions. The primary structure of HETPRO has been optimized in a guided fashion, from an antimicrobial peptide, for transmembrane orientation, defined 3D structure, and functions. HETPRO assembles into a tetrameric form, from an apo dimeric helical structure, in complex with cofactor in detergent micelles. The NMR structure of the apo HETPRO in micelles reveals an antiparallel helical dimer that inserts into the nonpolar core of detergent micelles. The well-defined structure of HETPRO and its ability to bind to heme moieties could be utilized to develop a functional membrane protein mimic for electron transport and photosystems.